2009
DOI: 10.1126/science.1169727
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the Glycosyltransferase Sxc/Ogt in Polycomb Repression

Abstract: Putting the Sugar on Polycomb A wide variety of nuclear and cytosolic proteins in human cells carry an O-linked sugar modification, N -acetylglucosamine (GlcNAc), which is added by the highly conserved O-linked GlcNAc transferase, Ogt. Gambetta et al. (p. 93 , published online 28 May; see the Perspective by Simon ) show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
355
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(370 citation statements)
references
References 21 publications
15
355
0
Order By: Relevance
“…3). This and other results of the present study support previous observations that OGT and EZH2/PRC2 are functionally associated with each other (34,35,37). Nevertheless, discrepancy still exists.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…3). This and other results of the present study support previous observations that OGT and EZH2/PRC2 are functionally associated with each other (34,35,37). Nevertheless, discrepancy still exists.…”
Section: Discussionsupporting
confidence: 80%
“…Three of the PRC1 components, Ph, Pc, and Ring, are likely Sxc/Ogt substrates in Drosophila (34). However, these observations have not been confirmed by mass spectrometry analysis, and no function has been reported with regard to the O-GlcNAcylation of these proteins (34). In the present study, using an unbiased small-scale screening, we independently demonstrate that OGT depletion leads to the downregulation of H3K27me3.…”
Section: Significancementioning
confidence: 47%
See 1 more Smart Citation
“…2A). GRMZM2G477503 is annotated as a glycosyl transferase, a protein that can potentially be involved in polycomb repression (30). Results of 5′ and 3′ RACE showed that ZmMNC-18 is transcribed in the same direction as GRMZM2G477503 and has a poly(A) tail (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…OGT is essential for embryonic stem cell viability and somatic cell function (O'Donnell et al 2004;Shafi et al 2000). Deletion of OGT in Arabidopsis (Jacobsen et al 1996), Drosophila (Sinclair et al 2009;Gambetta et al 2009), and mice is lethal (Shafi et al 2000), and leads to dauer phenotypes in Caenorhabditis elegans (Hanover et al 2005), suggesting that O-GlcNAc is essential for cellular homeostasis.…”
Section: O-glcnac Transferasementioning
confidence: 99%